PENGGUNAAN MOBIL PELAYANAN KELILING UNTUK MENINGKATKAN PENERIMAAN PAJAK BUMI DAN BANGUNAN PERDESAAN DAN PERKOTAAN TAHUN 2023-2024 DESA SUKAKARYA KABUPATEN BEKASI - Dahuri, Adin; Yani, Yani; Syadat, Fahrul Anwar; Anastasya, Amanda (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
The 2021 PBB revenue achievement of Sukakarya Village was 39.82% and in the beginning 2022 decreased to 6.78% so that a strategy was established in the form of providing and operating a Mobile Service Car as an effort to provide better service for residents in paying PBB. This descriptive research with a qualitative approach seeks to determine the effect of the use of Mobile Service Car to increase PBB revenue in Sukakatya Village in 2023-2024. The results of the study indicate that at the beginning of 2023 the PBB revenue achievement was 19.75%, not yet a drastic increment because residents were still in the adjustment stage from previous payment model to the payment model through the Mobile Service Car. The PBB revenue achievement at the end of 2024 was 43.50% due to the positive contribution of several things, namely convenience, placement of the Car at the Village office, operating schedule during the Minggon Meeting, no need to queue, fast service process, -submission of Tax Payment Evidence and special operational schedule after harvest. Based on the description, it can be generally concluded that the use of the Mobile Service Car has a positive impact on increasing the PBB revenue of Sukakarya Village in 2023-2024.